2023
DOI: 10.3233/jpd-225116
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise as a Potential Treatment for Fatigue in Parkinson’s Disease? A Systematic Review and Meta-Analysis of Pharmacological and Non-Pharmacological Interventions

Ann-Kristin Folkerts,
Jörn Nielsen,
Romina Gollan
et al.

Abstract: Background: Fatigue is one of the most common and debilitating non-motor symptoms among patients with Parkinson’s disease (PD) and significantly impacts quality of life. Therefore, effective treatment options are needed. Objective: To provide an update on randomized controlled trials (RCTs) including pharmacological and non-pharmacological (but non-surgical) treatments that examine the effects of fatigue on PD patients. Methods: We searched the MEDLINE, EMBASE, PsycINFO, CENTRAL, and CINAHL databases for (cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“… 5 Several studies have shown that generic exercise in ordinary life and physiotherapy have a symptomatic benefit on general motor features, depression, and fatigue in PD patients. 6 7 8 Furthermore, studies using PD animal and patient models have found that regular exercise can enhance brain-derived neurotrophic factor (BDNF) production, mitophagy in neurons, and antioxidant expression. 8 9 Exercise-induced mitophagy is expected to reduce the deposition of toxic α-synuclein aggregates, and may delay the onset or progression of PD.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Several studies have shown that generic exercise in ordinary life and physiotherapy have a symptomatic benefit on general motor features, depression, and fatigue in PD patients. 6 7 8 Furthermore, studies using PD animal and patient models have found that regular exercise can enhance brain-derived neurotrophic factor (BDNF) production, mitophagy in neurons, and antioxidant expression. 8 9 Exercise-induced mitophagy is expected to reduce the deposition of toxic α-synuclein aggregates, and may delay the onset or progression of PD.…”
Section: Introductionmentioning
confidence: 99%